KAITAN PENGGUNAAN ANALGETIK DAN OBAT ANTI INFLAMASI NON STEROID DENGAN KEJADIAN GAGAL GINJAL KRONIK PADA PASIEN HEMODIALISA DI RSU PKU MUHAMMADIYAH YOGYAKARTA - , Woro Supadmi, SSi, Apt.; , Prof. Lukman Hakim, M.Sc., Ph.d.,Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Chronic renal failure is a matter of health, social and economi with increasing incidence, prevalence and morbidity. This study was aimed to observe assosiation between the used of analgesics and NSAIDs and calculate odds ratio of chronic renal failure incidence at PKU Muhammadiyah Hospital in Yogyakarta. The study used analytical observation with case control desingn,group of case cosisted as chronic renal failure patients who do hemodialysis, group of control who are not diagnosed with chronic renal failure. Secondary data were obtained from patientâs medical records , the primary data were obtained through indepth interview by guided questionnaire.. Data analysis was using the 2 x 2 table and analyzed with chi square test to find out the correlation and the odds ratio between the use of analgesics and NSAIDs of chronic renal failure incidance. The used of analgesics not assosiation of chronic renal failure incidence (OR:0.1 ,p>0.05